Voltage Regulation Considering BESS in Microgrids with High Photovoltaic Generation Penetration - Rodriguez Melendez, Hector Ismael; Beteta Susanibar, Brian Jesus; Villavicencio Gastelu, Joel; Obispo Vásquez, Angel Eduardo (LACCEI, 2025)
In microgrids with high photovoltaic (PV) generation penetration, voltage regulation has emerged as a critical challenge owing to inherent variability in power production. This study evaluates the effectiveness of battery energy storage systems (BESS) in mitigating voltage fluctuations by applying droop-control techniques. Among the various microgrid control strategies, droop control is the most significant. In addition to this conventional approach, in this work, the state-of-charge (SoC)-based control for the BESS was implemented, enabling more dynamic voltage regulation in response to system variations. Simulations were conducted to assess control performance under two scenarios: (1) a microgrid with BESS regulated solely through conventional droop control, where a voltage drop to 0.87 p.u. was observed, stabilizing at 1.025 p.u. within 41 ms; and (2) a microgrid with BESS regulated using a combination of droop control and SoC-based control, resulting in a voltage drop to 0.892 p.u., with stabilization at 1.01 p.u. achieved in just 20 ms. The results demonstrate that the proposed methodology maintains a voltage within permissible limits while achieving faster response times than the conventional approach.